1991
DOI: 10.1063/1.859762
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of finite-amplitude ionization wave packets excited in He positive columns

Abstract: Spatiotemporal structures of large-amplitude ionization wave packets excited in a He positive column are reconstructed by the technique of computerized tomography (CT), The CT approach allows the use of sophisticated techniques to obtain radially resolved spectral images far superior to those from the more usual Abel inversion. Phenomena such as complicated ionization front interactions of the type modeled by Grabec [Phys. Fluids 117, 1834 (1974) ] from the Pekarek equations are clearly seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The reason for this agreement lies in the coincidence of the radial structure of the homogeneous column with the radial structure of the ionization wave. This behaviour was confirmed experimentally by Ohe et al (1991), The solid line shows the exact solution with almost-vanishing nonlinear damping (Im(Q) ≈ 0.01), the long-dashed line correponds to a solution with coefficients calculated when the radial structure is neglected (Im(Q) ≈ 0.16). Finally, the short-dashed line is obtained when the dispersive damping is changed to growth (Im(Q) ≈ −2.5).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The reason for this agreement lies in the coincidence of the radial structure of the homogeneous column with the radial structure of the ionization wave. This behaviour was confirmed experimentally by Ohe et al (1991), The solid line shows the exact solution with almost-vanishing nonlinear damping (Im(Q) ≈ 0.01), the long-dashed line correponds to a solution with coefficients calculated when the radial structure is neglected (Im(Q) ≈ 0.16). Finally, the short-dashed line is obtained when the dispersive damping is changed to growth (Im(Q) ≈ −2.5).…”
Section: Resultssupporting
confidence: 61%
“…It turns out that the eigenfunctions are almost independent of the wavenumber k. This partly justifies the previously used reductions to one spatial coordinate, as will also become clear later from the numerical simulations. The radial structure of ionization waves was measured by Ohe et al (1991). Their results also show the almost-identical forms of the radial profils of the positive column and the ionization wave.…”
Section: Linear Equations At First Ordermentioning
confidence: 84%
“…P and Q are complex coefficients which have been determined analytically (including the radial structure). It should be mentioned that all the predictions agree very nicely with experimental results [22], even for the three-dimensional structure. The Ginzburg-Landau equation typically expresses what in words is, for example [19], explained as: 'Low-amplitude waves obeying liner theory typically survive under conditions that correspond to moderate penetration into the instability region'.…”
Section: Striated Columns: the Universal Behaviour Of Single Modessupporting
confidence: 81%
“…Some observations [20], using an optical absorption technique for spectraJ lines corresponding to the transition of metastables, have shown that the radial profile slightly differs from the charged-particle profile. The optical structure in the radial direction can be detected with good accuracy by an image reconstruction using a CT technique [21,22], because the self-absorption may be neglected as described previously [23,24] optical radiation from the column was detected with a slit-monochromator which was movable in the radial direction at the same axial position as that of the probe installation. Since the grid installation causes an axially symmetric profile, sufficient projection data can be obtained by moving the monochromator from the tube axis to the wall.…”
Section: Methodsmentioning
confidence: 99%